Structure and thermal stability in hydrophobic Pluronic F127-modified silica aerogels - Fermino, Taína Z. [UNESP]; Awano, Carlos M. [UNESP]; Moreno, Leandro X. [UNESP]; Vollet, Dimas R. [UNESP]; de Vicente, Fabio S. [UNESP] (Elsevier, 2018)
Hydrophobic ambient pressure drying (APD) aerogels were prepared from hydrolysis of tetraethylorthosilicate (TEOS) in solutions with different concentrations of poly(ethylene oxide)–poly(propylene oxide)–poly(ethylene oxide) (F127). APD was carried out after silylation of wet gels with 20% by volume of hexamethyldisilazane (HMDZ) in n-hexane. The samples were analyzed by small-angle X-ray scattering (SAXS) and nitrogen adsorption. The APD aerogels obtained in this process were submitted to heat treatment at 300, 500, 700 and 900 °C to study the pores stability. The samples were characterized by nitrogen adsorption. Wet gels are formed by mass-fractal domains, with fractal dimension close to 2.1 and characteristic size (ξ) spanning from about 9 nm (for the gel prepared without the addition of F127) up to values that exceed the maximum limit of the SAXS experimental setup, with increasing the concentration of F127. Nitrogen adsorption data showed that the pore volume (Vp) and the mean pore size (lp) of the aerogels increased with increasing the concentration of F127. The drying process diminished the characteristic size ξ and increased the dimension D of the mass-fractal domains and the size (r0) of the primary particles of the aerogels with respect to the wet gels. The characteristic size ξ of the mass-fractal of the aerogels was found significantly larger with increasing the concentrations of F127. Thermally treated aerogels exhibited a similar general behavior with temperature independent of the concentration of F127. The porosity was found fairly stable up to about 500 °C. The porosity started to be eliminated at 700 °C and it was found practically collapsed at 900 °C. The silylation layer on the silica surface of the present APD aerogels was promptly eliminated at about 350 °C yielding complete loss of hydrophobicity.
Keywords: Hydrophobic aerogels; Nitrogen adsorption; SAXS; Thermal treatment; Thermogravimetric analysis